100 GHz Room-Temperature Laboratory Emission Spectrometer. Issue Volume 13:Issue S332(2017) (4th September 2018) - Wehres, Nadine; Heyne, Bettina; Lewen, Frank; Hermanns, Marius; Schmidt, Bernhard; Endres, Christian; Graf, Urs U.; Higgins, Daniel R.; Schlemmer, Stephan
Abstract: We present first results of a new heterodyne spectrometer dedicated to high-resolution spectroscopy of molecules of astrophysical importance. The spectrometer, based on a room-temperature heterodyne receiver, is sensitive to frequencies between 75 and 110 GHz with an instantaneous bandwidth of currently 2.5 GHz in a single sideband. The system performance, in particular the sensitivity and stability, is evaluated. Proof of concept of this spectrometer is demonstrated by recording the emission spectrum of methyl cyanide, CH3 CN. Compared to state-of-the-art radio telescope receivers the instrument is less sensitive by about one order of magnitude. Nevertheless, the capability for absolute intensity measurements can be exploited in various experiments, in particular for the interpretation of the ever richer spectra in the ALMA era. The ease of operation at room-temperature allows for long time integration, the fast response time for integration in chirped pulse instruments or for recording time dependent signals. Future prospects as well as limitations of the receiver for the spectroscopy of complex organic molecules (COMs) are discussed.